Effectiveness, Safety, and Patterns of Real-World Isavuconazole Use in Europe (2015–2019) - Dionysios Neofytos; Antonio Pagliuca; Katherine Houghton; Edward Broughton; Maria Lavinea Novis de Figueiredo Valente; Lili Jiang; David A. Enoch; Beate Gruener; Raoul Herbrecht; Tobias Lahmer; Olivier Lortholary; Cléa Melenotte; et al. (Infectious Diseases and Therapy)
Abstract Introduction Real-world data from multinational observational studies are required to better understand the role and performance of isavuconazole in real-world practice in Europe. Methods A retrospective medical record review was conducted at 16 sites in Europe (France, Germany, Italy, Spain, and the United Kingdom). Eligible records were from patients aged ≥ 18 years at the time of isavuconazole initiation and received at least one dose of isavuconazole for suspected or confirmed invasive aspergillosis (IA) or invasive mucormycosis (IM) during the eligibility period (October 15, 2015 to June 30, 2019). Data were descriptively analysed. Success rates, overall survival, and times to these events were descriptively analysed. Results Data were abstracted from 218 patients (201, IA; 17, IM) who received isavuconazole as monotherapy (initiated as infusion, 52%; oral, 46%). Isavuconazole was initiated as primary therapy in 92 patients (42.2%) and salvage therapy in 121 patients (55.5%) (unknown for five patients). Mean (standard deviation) age was 56.8 (15.6) years, 66% were men and 62% had at least three comorbidities, most frequently haematologic malignancy (62%). Estimated clinical response rate at week 24 was 54.5% (95% confidence interval [CI], 38.2–66.5%) for primary treatment and 73.5% (95% CI, 62.7–81.1%) for salvage therapy. Overall, 45 patients (21%) experienced at least one adverse event (AE). Serious AEs were experienced by 37 patients (17%), with seven related to isavuconazole; five patients (2.3%) discontinued isavuconazole monotherapy due to the serious AE. A total of 137 patients (63%) died, with 17 deaths (12.4%) related to their invasive fungal infection, 11 of whom initiated isavuconazole as salvage therapy. Conclusions This study adds to the growing body of evidence that whether used as first-line therapy or after the failure of other antifungal therapies, isavuconazole appears to have a promising clinical response and a good safety profile as an antifungal agent in patients with varied underlying conditions.